MODEL PRODUKSI BIOETANOL DARI LIMBAH KEJU MENGGUNAKAN KLUYVEROMYCES MARXIANUS - Rudy Agustriyanto; Akbarningrum Fatmawati (Jurnal Teknik Kimia USU, 2013)
The depletion of oil reserves hasbeen increasing interest in the development of alternative renewable energysources. Cheese whey as a waste of cheese production is one of the raw materials that can be used for bioethanol production. The aim ofthis study is to conduct critical assessment of the cheese whey fermentation process by applying the basic concepts of engineering and mathematics, to investigate the characteristics of the cheese whey fermentation process into bioethanol, and to obtain the optimum design of fermenter. This is done by developing steady state model of cheese whey fermentation system into ethanol based on kinetic data from previous research and using mass balance principle.The model was then used to simulate the continuous fermentation of cheese whey for ethanol production. At steady state conditions, the fermentation process of cheese whey into bioethanol is affected by the hydraulic retention time (R). At steady state conditions, the optimum value of R obtained is 25 hours based onhigh ethanol productivity. The results of this study will be useful in the design process and control of cheese whey fermentation reactions into ethanol.The utilization of waste from cheese production (cheese whey) that contain sugars which can be fermented will provide added value to the waste while providing an alternative source of renewable energy that is needed due to energy crisis.